HUBUNGAN KEMAMPUAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS PARAGRAF ARGUMENTASI SISWA KELAS X SMA NEGERI 1 SUNGAI PUAR KABUPATEN AGAM - Sari, Ria Novita; Abdurahman, Abdurahman; Marni, Silvia (Pendidikan Bahasa Indonesia, 2013)
These researches are for: (1) description of ability and export students in X grades high school 1 Sungai Puar, Agam, (2) description writing argumented students in X grades high school 1 Sungai Puar, Agam, (3) description relation between writing with skills how to write argumented paragraf students in X grades high school 1 Sungai Puar, Agam.            These researches used quantitative approach with descripted metode results of  research are from 2 tried out: objective and performance. Objective tried out used for gathering data, whereas performance used for gathering data of writing skills of argumented paragraf. Are exsampel of these researches are 32 people, we ased propotionat technique random sampling take out 24 % from all of students per class.            Base this research and data analysis, conclated : 1st understand reading students of high school 1 Sungai Puar, Agam resulted in good qualification (74,25), 2nd skiils of writing argumented paragraf resulted enough qualification (70,46), 3nd there were signifant relation between understanding read and skills of writing argumented paragraf, because of improving resulted t sount > t tabel (4,098 > 2,750). 0,60 so that writing and reading have significan relation.